Translation and Meaning. New Series, Vol. 2, Pt. 2 - Bogucki, Lukasz; Bogucki, Lukasz (Peter Lang, 2016)
The volume contains a selection of articles on current theoretical issues in audiovisual translation, translator training and domain-specific issues. The authors are experts in their fields from renowned universities in the world. The book will be an indispensable aid for trainers and researchers, but may be of interest to anyone interested or active in translation and interpreting. A companion volume in this series contains articles on Translation Studies and literary translation.